Astrocytic cystine/glutamate antiporter is a key regulator of erythropoietin expression in the ischemic retina. Issue 5 (11th February 2019) - Lee, Byung Joo; Jun, Hyoung Oh; Kim, Jin Hyoung; Kim, Jeong Hun
ABSTRACT: Ischemic retinopathies and optic neuropathies are important causes of vision loss. The neuroprotective effect of erythropoietin (EPO) in ischemic neuronal injury and the expression of EPO and its receptor in retinal tissue have been well documented. However, the exact regulatory mechanism of EPO expression in retinal ischemia still remains to be elucidated. In this study, we investigated the role of cystine/glutamate antiporter (system xc − ) in the regulation of astrocytic EPO expression by using both in vitro and in vivo models. Under hypoxia, the expression of astrocytic system xc − is up‐regulated both in vitro and in vivo . Inhibition of system xc − resulted in depletion of intracellular glutathione (GSH) and decrement of GSH disulfide ratios in human brain astrocytes (HBAs). In HBAs, hypoxia‐induced stabilization of hypoxia‐inducible factor (Hif)‐2α is nearly completely abolished by inhibition of system xc − . Hypoxia‐induced up‐regulation of astrocytic EPO expression is suppressed by both pharmacological inhibition and siRNA‐mediated knockdown of system xc − . In contrast, basal EPO expression under normoxia is not affected by system xc − modulation. In summary, under hypoxia, increased system xc − acts as the major source of intracellular GSH, which helps in stabilizing Hif‐2α and subsequent up‐regulation of EPO in astrocytes.—Lee, B. J., Jun, H. O., Kim, J. H., Kim, J. H. Astrocytic cystine/glutamate antiporter is a key regulator of erythropoietin expression in the ischemic retina. FASEB J. 33, 6045–6054 (2019). www.fasebj.org